Geometric Morphometric Analysis of two genera confirm three new wasps from the mid-Cretaceous of Myanmar (Hymenoptera: Aulacidae). (February 2022) - Li, Longfeng; Shih, Peter J.M.; Zhang, Xiaoqing; Peng, Cuo; Li, Daqing; Ren, Dong
Abstract: Three new species, Exilaulacus advenus sp. nov., Exilaulacus eximius sp. nov. and Electrofoenops exaltatus sp. nov. in two genera of Aulacidae, are described and figured based on three well-preserved specimens from the mid-Cretaceous Myanmar (Burmese) amber. Forewings of four described fossil species of Aulacidae and the three new species are studied by using the Geometric Morphometric Analyses (GMA) to further confirm their taxonomic classifications.